PENGARUH PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN PAJAK DAN KESADARAN PERPAJAKAN TERHADAP MOTIVASI WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK - Suryawati; Siti Rodiah; Mentari Dwi Aristi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study is a quantitative research that aims to determine the influence of tax knowledge, tax service quality and tax awareness on the motivation of individual taxpayers in paying taxes. This research was carried out directly in the field by distributing questionnaires to respondents at KPP Pratama Pekanbaru Tampan. The population used was individual taxpayers, both employees and non-employees, who were registered at KPP Pratama Pekanbaru Tampan with sampling using the slovin formula as many as 278 respondents. The data analysis techniques used in this study are descriptive statistical analysis, data quality test, classical assumption test and hypothesis test. The results of this study show that tax knowledge, quality of tax services and tax awareness affect the motivation of individual taxpayers in paying taxes at KPP Pratama Pekanbaru Tampan so that it can increase tax revenue.